The Executorial Nature of Fiduciary Guarantee Certificates as Equivalent to Final and Binding Court Decisions - Ahmad Badawi; Nikmatul Keumala Nofa Yuwono (Rechtenstudent, 2024)
In the fiduciary guarantee certificate, the phrase “For the Sake of Justice Based on God Almighty” is included, which grants it the same executorial power as a court decision with permanent legal force, as regulated in Article 15 of Law Number 42 of 1999 on Fiduciary Guarantees. This study examines three main problems: first, the function of the principles of publicity and speciality in fiduciary guarantee registration; second, the legal force of the fiduciary guarantee certificate; and third, its position as the basis for execution of fiduciary guarantee objects. The research adopts a doctrinal method aimed at systematically explaining legal rules, analyzing interrelations among them, clarifying obscure aspects, and predicting future developments. The approach combines statutory, conceptual, and historical perspectives, employing both primary and secondary legal materials, alongside non-legal references, analyzed through a deductive-qualitative method. The principle of publicity functions to ensure accessibility in identifying fiduciary objects, while the principle of speciality provides legal certainty to fiduciary recipients. However, the fiduciary guarantee certificate is issued by the Ministry of Law, which does not possess the authority to grant executorial power. Therefore, from a theoretical standpoint, the fiduciary guarantee certificate should not equate to a court decision with permanent legal force but rather serve merely as proof of registration containing the statement “For the Sake of Justice Based on God Almighty.” This reveals a normative contradiction between statutory regulation and the practical interpretation of the certificate’s legal force”.